Implikasi Merger Kelurahan terhadap Pelayanan Publik di Kelurahan Kauman Kota Pekalongan - Rosaninda Febry Suryanie; Puji Astuti (Journal of Politic and Government Studies, 2018)
Merger policy of village is implemented by local government of Pekalongan city as a form of bureaucratic reformation in public services. Based on local regulation (Perda) Kota Pekalongan Nomor 8 Tahun 2013, the implementation of merger policy of village leads to improving the services to be more effective and efficient. The aim of the research is to understand the implications of merger policy in village toward Public Services in Kauman Village Pekalongan City.The research uses mix methods, which merges the type of qualitative and quantitative method. Questionnaire method is used as the quantitative method, which is spread to 68 respondents in Kauman Village with SERQUAL approach by Parasuraman, which consists of tangible, reliability, responsiveness, assurance, empathy variable. Respondents are determined by accident sampling. Meanwhile, the qualitative one consists of primer and secondary data, so they complete the data which is found by the quantitative one. Researcher uses in-depth interview and study of the document as the qualitative one.The result shows that village merger policy in Kauman village works out and fits with the goal of merger policy, which is improving the effectivity and efficiency of public services. It can be seen from the average score of the assessment by the community towards public services is 45.5, and it categorizes at good level.  The score of each variable is tangible has score 12.75, reliability score is 9.94. Both of them are good average. And the responsiveness score is 6.66, the assurance score is 9.91, and the empathy score is 6.73. Both the responsiveness and assurance variable are very good average, meanwhile the assurance variable is very good average.But there are a few things that have to be improved from the merger policy in Kauman village, such as improving the human resources of the village government such as improving their IT (Information and Technology) skills, the discipline of the staffs, the existence of suggestion box, and queue number for the services.Keywords : village merger policy, public service